The use of a smartphone app for self-monitoring by patients with bipolar disorder being treated in a primary care setting - Omar H. Elsayed; John Cecil; Richard Priesmeyer; Gregg Siegel; Phyllis Siegel; Rif S. El-Mallakh (Journal of Family Medicine and Primary Care)
Background: Self-monitoring and self-management are growing phenomena in the care of chronic illnesses, like bipolar disorder. A significant fraction of patients with bipolar disorder are cared for by primary care providers. The use of smart technology may be effective in this setting. Method: KIOS-Bipolar, a smartphone app that proved superior in a randomized, controlled trial, was beta-tested for two-month periods in 12 patients with bipolar disorder who were under the care of a primary care clinic. Results: Adherence to the app was 100%. Patients experienced improvements in depressive (−41%) and manic (−46%) symptoms and overall instability (−39%). Patients felt that the system was user-friendly with an average system usability score of 80.8 (range 48–100). Five participants (41.8%) gave a system usability score ≥ 90. Discussion: This open trial suggests that utilization of a self-management tool may be a useful adjunct in the treatment of patients with bipolar disorder in the primary care setting.